Ripercorrere la Roma Quadrata - Intervista a Piero Meogrossi - MediaGEO, Redazione (Archeomatica, 2024)
The interview discusses how paintings like those by Mantegna and Leombruno depict ancient Rome, blending myth and history to celebrate the religious power and humanistic culture of the 15th century, while suggesting a labyrinthine topography of the eternal city, integrating Christian and pagan elements into a complex symbolic and political fabric.